2010
DOI: 10.1002/hed.21483
|View full text |Cite
|
Sign up to set email alerts
|

Nasal morbidity following endoscopic skull base surgery: A prospective cohort study

Abstract: Nasal morbidity following endoscopic skull base surgery is common and may be affected by surgical complexity and use of the nasoseptal flap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
186
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(199 citation statements)
references
References 22 publications
9
186
1
3
Order By: Relevance
“…2,3,6,13,16,19 These results are providing practitioners with valuable information for managing patient expectations and modifying surgical technique to optimize QOL. A summary of recent findings is reported in Table 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,6,13,16,19 These results are providing practitioners with valuable information for managing patient expectations and modifying surgical technique to optimize QOL. A summary of recent findings is reported in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not examine the impact of extent of tumor resection on sinonasal QOL, although McCoul et al reported subtotal resection as a negative prognostic factor. 13 Pant et al 15 studied 51 patients and de Almeida et al 6 studied 63 patients from the same institution and noted that the use of an extended approach was a negative prognostic factor. 15 These studies have methodological limitations that impact the authors' conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies evaluating sinonasal morbidity after endoscopic endonasal skull base surgery have found that there is a 3-to 4-month period of increased sinonasal morbidity associated with these procedures. 11,13,14,17,18 After this early period of increased sinonasal morbidity, improvements in sinonasal symptoms compared with preoperative levels following endoscopic endonasal skull base surgery have been shown. 14,18,19 The most common sinonasal complaints after endoscopic endonasal skull base surgery included nasal crusting, nasal discharge, nasal airflow blockage, and disturbances in olfaction.…”
Section: Discussionmentioning
confidence: 99%
“…The most used Introduction are the Sinonasal Outcome Test 20 (SNOT-22), Rhinosinusitis outcome measure (RSOM-31) and the Rhinosinusitis Disability Index (ISDN). In one of the first studies about posterior nasal symptoms in skull base surgery, de Almenida et al [3] observed that the most frequent finding one month postoperative were nasal crusts (98%), and at least half of the patients continue with nasal crusts for 3 months post-surgery; the time of disappearance of the crusts was related to the complexity of the surgery but not to the use of fat or flaps to close the defect of the skull base. Recently, Alobid et al [2] studied a series of patients undergoing transsphenoidal ESBS (38 patients) or extended surgery with nasoseptal flap reconstruction (17 patients), they observed that in the postoperative period 28% of the patients who undergone transsphenoidal approaches and 64% who undergone extended surgery had posterior rhinorrhea.…”
Section: Sinonasal Symptomsmentioning
confidence: 99%
“…The progress and development of these endoscopic techniques are mainly due to the ever increasing knowledge of endoscopic anatomy, technological advances and the use of vascularized flaps for reconstruction of the skull base [1]. As in endoscopic sinus surgery the extended approaches can cause a series of postoperative morbidities, like crusting and posterior rhinorrhea, especially in those cases requiring a nasoseptal flap reconstruction [2,3]. All sinus surgery could cause a mechanical damage of the sinus mucosa, which would require a subsequent healing process.…”
mentioning
confidence: 99%